2013
DOI: 10.2217/fvl.12.136
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr Virus and Autoimmunity: The Role of a Latent Viral Infection in Multiple Sclerosis and Systemic Lupus Erythematosus Pathogenesis

Abstract: Multiple sclerosis (MS) and systemic lupus erythematosus (SLE) are both chronic autoimmune diseases with unknown etiology. To date, EBV is the most closely implicated infectious agent to be associated with both MS and SLE. Epidemiological findings show a strong correlation between EBV infection and the risk of developing these diseases. The type and magnitude of both EBV-specific antibodies and T-cell responses produced by MS or SLE patients are dysregulated when compared with healthy cohorts. Despite all thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Certain experimental studies indicated a connection between an abnormal immune response to EBV and SLE; more concisely, it has been observed that SLE patients developed specific anti-EBV IgG antibodies that were absent in healthy controls, and vice versa ( 57 ). From an epidemic point of view, EBV infection is associated with a higher risk of developing SLE and other autoimmune diseases, such as multiple sclerosis ( 58 ). As EBV infects B cells (and other immune cells) inducing the production of pro-inflammatory cytokines, this fact and an aberrant immune response to this virus could be linked to SLE.…”
Section: A Role For the Virome In Sle?mentioning
confidence: 99%
“…Certain experimental studies indicated a connection between an abnormal immune response to EBV and SLE; more concisely, it has been observed that SLE patients developed specific anti-EBV IgG antibodies that were absent in healthy controls, and vice versa ( 57 ). From an epidemic point of view, EBV infection is associated with a higher risk of developing SLE and other autoimmune diseases, such as multiple sclerosis ( 58 ). As EBV infects B cells (and other immune cells) inducing the production of pro-inflammatory cytokines, this fact and an aberrant immune response to this virus could be linked to SLE.…”
Section: A Role For the Virome In Sle?mentioning
confidence: 99%
“…Once the virus is deactivated by immune system, it resides dormant inside of B cells . Reactivation can occur later in life when the host is under stress resulting in chronic fatigue and autoimmune diseases . Epstein‐Barr virus nuclear antigen‐1 is a transcriptional regulator of latent replication and, essential for the maintenance of the viral episome within the host …”
Section: Introductionmentioning
confidence: 99%